Role of a ketogenic diet on body composition, physical health, psychosocial well-being and sports performance in athletes: A scoping review - Bowler, A.-L.; Polman, R. (Sports, 2020)
Background: Recently, a focus has been placed on investigating the potential benefits of adherence to a ketogenic diet in enhancing body composition, physical health, psychological well-being, and performance of athletes from various sporting disciplines. As the available research is yet to be collated and analyzed in a single review, this scoping review aims to analyze and draw conclusions from the available literature that exists on the efficacy of a ketogenic diet among athletic populations. Methods: Several primary research databases and any relevant citation lists were searched to locate appropriate studies for inclusion in this scoping review. Studies that investigated the effects of adherence to a ketogenic diet (KD), defined by a carbohydrate intake of less than 5% of total energy intake, on body composition, physical health, psychological well-being, and performance among an athletic population were included in the review. From 814 articles screened, 12 were identified as meeting the inclusion criteria and were included in the final scoping review. Results: Adherence to a KD has beneficial effects on body weight and fat mass. Varying effects were identified on physical health with the diet, eliciting positive effects on fat oxidation but potentially deleterious effects on stool microbiota and iron metabolism. Conflicting results were reported regarding the effects of a KD on sporting performance. Benefits were reported regarding athlete well-being following commencement of a KD, but only after week two. Conclusions: The results of this scoping review demonstrate that there are both beneficial and detrimental effects associated with adherence to a KD among athletic populations. It is understood that further research is required to make any concrete recommendations regarding a KD to athletes.